Systematics of Potamanthodes nanchangi Hsu, 1936 (Ephemeroptera: Potamanthidae) - Li, Wen-Juan; Mu, Peng-Xu; Zhou, Chang-Fa (Zootaxa, 2022)
The enigmatic mayfly Potamanthodes nanchangi Hsu, 1936 was briefly described based on a male. Currently, this species has an unclear taxonomic position and no supporting type specimen, consequently its recognition, differentiation and classification is vague. In this study, by using fresh specimens from type locality in Jiangxi province at central China, this species is redescribed, photographed, and a neotype is designated. This species evidently belongs to the genus Potamanthodes Ulmer, 1920 by its short mandibular tusks (shorter than head), presence of setae row on forefemora of nymphs, slender and deeply bifurcated V-shaped penes, common base of MP2 and CuA of forewings. Significant morphological characters defining this species are relatively long penial tips, greatly bent R1 of hindwings and small compound eyes of the males, large mandibular tusks and long forelegs of the nymphs. Therefore, the P. nanchangi is indeed a valid and apomorphic species in the genus Potamanthodes.